AN INVESTIGATION INTO MODALITY EXPRESSIONS IN ENGLISH FILM SUBTITLES AND THEIR CORRESPONDING EXPRESSIONS IN THE VIETNAMESE - Lê Vương Song Hà (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Up to now, issues of modality expressions have been addressed with more interest in such lexical means and grammatical means as modal adverbs, modal auxiliary verbs, modal lexical verbs and mood system. Based on a broader view of modality, this study aims to examine prosodic means, communicative types of sentences and modal particles used in conversations in English films and Vietnamese subtitles. The research was conducted with a descriptive study that sought the qualitative and quantitative information about the types of modality expressions used in English films and their corresponding expressions in Vietnamese subtitles. Based on the qualitative and quantitative analysis of a sample of 788 utterances collected from 10 English films and their Vietnamese translated sentences, the study found that different communicative types of sentence were used to signal the speech act modality with illocutionary force along with the modal nuances conveyed by various intonation patterns. The study also reveals that the choice of modal particles in the Vietnamese translation of the subtitles with different emotion and attitude were governed by a number of pragmatic factors such as the information of the particular communicative situation or the relationships between the utterances, the information that signals the speaker’s supposition to the hearers status of mind and knowledge, the information that signals the social status, role of the interlocutors or communicative partners, the information that orientates the response or feedback from the other interlocutors.